Stenonite a new carbonate-fluoride from Ivigtut, South Greenland - Pauly, Hans (Meddelelser om Grønland, 1962)
In the revised edition of the Mineralogia-Groenlandica (The Mineralogy of Greenland, O. B. BØGGILD (2)). BØGGILD mentions the occurrence of small grains of an unknown mineral in a baryte-jarlite sample from Ivigtut. The sample was given to the Mineralogical Museum in 1926. Additional finds of small grains of the mineral were made in 1953 by the author. In 1955 the mineral was found in cm sized specimens in a matrix of jarlite, and during the summer of 1961 many pieces were collected in the Ivigtut cryolite mine, where the mineral also was found in situ. The composition of the mineral as calculated from the chemical analysis is Sr2AlCO3F5. It crystallizes monoclinically - presumably P21/m -, it has three directions of cleavage, along the basis and two prism faces. It is vitreous, colourless (white). The specific gravity is 3.86 and the hardness nearly 3½. The refractive indices are 1.452 and 1.538 for the lowest and highest indices, respectively. The axial angle has been measured at -2V ~ 43°. The mineral has been named after the famous Danish scientist NICHOLAUS STENONIS (NICHOLAUS STENO or in Danish NIELS STE(E)NSEN) (1638-1686) and given the name of Stenonite. Stenonite belongs to a paragenesis developed in the contact-zone between siderite-cryolite (common cryolite ore) and masses rich in fluorite, underlying the ore body in the eastern part of the mine. Cryolite has been replaced by jarlite, weberite and stenonite. The original sulphides have recrystallized and the siderite is partly altered to pyrite and hematite. The temperature interval for these processes seems to have been from about 200°C. and below.